(untitled) (Future Cities and Environment, 2022)
Throughout history, pandemics affect cities and their shapes, many health problems have been reflected in urban planning. Today, the world faces a general health crisis of COVID-19. The number of people infected by the virus and the increasing number of deaths may result in the city-design strategies. The effect of this pandemic shows the importance of urban design and its effect on viral infections and its role in the health of populations, but this relationship is unclear and ignored; that is why we face this pandemic today. In this study, we are looking to protect the environment and human health by enhancing air quality by designing a new urban space in crowded cities called ‘City Lung’ and green roofs to reduce the effect of air pollutions. Moreover, cleaning the air inside high-density districts by controlling pollution sources was a vital link observed between the lockdown and the reduction of CO2 emissions during the COVID-19 pandemic. This paper will start by searching for a crowded study area with high traffic density, study the impact of urban form and air quality effects on human health, and suggest solutions to this study area. In the beginning, ENVIMET 4.4.5 software was used to simulate the carbon emission values and validate these values by CI-340 lightweight hand-held photosynthesis system device to get readings to evaluate the urban air quality and its effect. The present study reveals that algae stations improved the oxygen ratio 1.65 times in the study area than the existing values. Also, green roofing as a solution effectively affects air quality near the ground, as an alternative for the green areas in crowded cities and pedestrians areas. This study enables urban planners to determine more greening principles for better urban living environments in high-density cities. Finally, the results give guidelines on improving air quality in the surrounding environment to enhance the quality of life.